Serbia and Montenegro : Serbia; Financial System Stability Assessment, including Reports on the Observance of Standards and Codes on the following topics; Monetary and Financial Policy Transparency, Banking Supervision, and Payment Systems. (IMF Staff Country Reports; Country Report ;, 2006)
This paper discusses key finding of the Assessment Reports on the Observance of Standards and Codes on Monetary and Financial Policy Transparency, Banking Supervision, and Payment Systems for Serbia. The assessment reveals that the transformation of Serbia's financial system is bringing important benefits, but there are emerging signs that the rapid pace of credit growth is beginning to erode financial stability. The main potential threat to financial stability is indirect credit risk arising from the large share of bank lending effectively denominated in foreign exchange.